Optimization & characterization of glipizide oral suspension formulation - Kalaiarasan, Muthusamy (2023)
Glipizide is an anti-diabetic medication which belongs to a class of drugs known as sulfonylurea. It is used with a proper diet and exercise program to control high blood sugar in people with type 2 diabetes. Glipizide can be a better alternative for metformin as an anti- hyperglycemic drug as it is more efficient in a smaller amount and imposes lesser side effects. Therefore, glipizide was used to make an anti- hyperglycemic drug suspension. In glipizide suspension, there are parameters like native starch, sodium carboxymethyl cellulose and Polysorbate 80 affecting its physical characteristics. There is a high chance for these parameters to interface and influence each other's effects on the suspension. Hence, it is essential to utilize an optimization method that can quantify the relationship between those two parameters, so that their amount in the suspension can be determined to make it perfect and optimum. Response Surface Methodology (RSM) is a combination of statistical and mathematical methods commonly used in the food industry to quantify the impacts of a few factors and to optimize conditions and thus applied in this study to optimize the production of glipizide suspension. In this study, preparation of suspension with parameters such as sodium CMC, native starch and Polysorbate 80 was investigated. The responses involved were viscosity and sedimentation rate. One Factor at One Time method was used to obtain the ranges for the aforementioned parameters. Then, using Design Expert software, the ranges of the parameters were entered in the Central Composite Design (CCD) to create 20 different combinations of parameters for formulation. After conducting the formulation, the values of viscosity and sedimentation rate obtained were keyed in Response Surface Methodology (RSM) for optimization. An optimum suspension was formulated and tested for sedimentation rate, mean particle diameter, viscosity, zeta potential measurement, in-vitro drug release and accelerated stability. Viscosity had an r2 value of 0.1633 and p value of 0.8510; whereas for sedimentation, r2 value was 0.0759 and p value was 0.9780. The sedimentation volume and viscosity of suspension are 0.0047462ml and 0.0039171Ns/m2 respectively. Zeta potential value is -38.63mV. During in-vitro drug release studies, the percentage of drug release is 98.80% after an hour. In conclusion, there is no significant effect on suspension due to individual parameters and their interactions. This study can be improvised by including in-vivo drug release study as well as changing the dosage form to nanoparticles. In-vivo drug release test will provide vi more information on the characteristics of the suspension whereas nanoparticles dosage form will help to reduce the quantity and toxicity of glipizide as well as increase its safety and efficacy.